They should stay there : the story of Mexican migration and repatriation during the Great Depression - Alanís Enciso, Fernando Saúl; Davidson, Russ; Overmyer-Velázquez, Mark (Chapel Hill : The University of North Carolina Press, 2017)
"Here, for the first time in English--and from the Mexican perspective--is the story of Mexican migration to the United States and the astonishing forced repatriation of hundreds of thousands of people to Mexico during the worldwide economic crisis of the Great Depression. While Mexicans were hopeful for economic reform following the Mexican revolution, by the 1930s, large numbers of Mexican nationals had already moved north and were living in the United States in one of the twentieth century's most massive movements of migratory workers. Fernando Sauʻl Alanís Enciso provides an illuminating backstory that demonstrates how fluid and controversial the immigration and labor situation between Mexico and the United States was in the twentieth century and continues to be in the twenty-first. When the Great Depression took hold, the United States stepped up its enforcement of immigration laws and forced more than 350,000 Mexicans, including their U.S.-born children, to return to their home country. While the Mexican government was fearful of the resulting economic implications, President Lázaro Cárdenas fostered the repatriation effort for mostly symbolic reasons relating to domestic politics. In clarifying the repatriation episode through the larger history of Mexican domestic and foreign policy, Alanís connects the aftermath of the Mexican revolution to the relentless political tumult surrounding today's borderlands immigration issues."--Page 4 of cover
Migratory movements between Mexico and the United States, 1880-1934 -- The Mexican community in the United States, 1933-1939 -- The Mexican government and repatriation: November 1934-June 1936 -- From the creation of the Demography and Repatriation Section to the elaboration of a repatriation project, July 1936-October 1938 -- The repatriation project, 1938-1939 -- Spanish refugees, the repatriated, and the Lower Rio Grande Valley -- The 18 March agricultural colony in Tamaulipas, 1939-1940 -- The end of the project, 1939-1940.
Translation of: Que se queden allá : el gobierno de México y la repatriación de mexicanos en Estados Unidos (1934-1940).
Includes bibliographical references and index.
Online resource; title from PDF title page (ProQuest Ebook Central, viewed August 5, 2019).
JSTOR
Keywords: Cárdenas, Lázaro, -- 1895-1970.; Cárdenas, Lázaro, -- 1895-1970.; Cárdenas, Lázaro, -- 1895-1970; Cárdenas, Lázaro -- 1895-1970; Mexican Americans -- History -- 20th century; Mexican Americans -- Employment -- History -- 20th century; Mexicans -- Employment -- United States -- History -- 20th century; Return migration -- Mexico -- History -- 20th century; Mexico -- Emigration and immigration -- History -- 20th century; Mexico -- Emigration and immigration -- Government policy -- History -- 20th century; United States -- Emigration and immigration -- History -- 20th century; Mexico -- Politics and government -- 1910-1946.; Américains d'origine mexicaine -- Histoire -- 20e siècle.; Américains d'origine mexicaine -- Travail -- Histoire -- 20e siècle.; Mexicains -- Travail -- États-Unis -- Histoire -- 20e siècle.; Migration de retour -- Mexique -- Histoire -- 20e siècle.; Mexique -- Politique et gouvernement -- 1910-1946.; États-Unis -- Émigration et immigration -- Histoire -- 20e siècle.; HISTORY -- United States -- State & Local -- General; Emigration and immigration; Emigration and immigration -- Government policy; Mexican Americans; Mexican Americans -- Employment; Mexicans -- Employment; Politics and government; Return migration; Mexico; United States; Migration; Rückwanderung; Mexikanischer Einwanderer; Mexikanischer Arbeitnehmer; Einwanderungspolitik; Repatriierung; Weltwirtschaftskrise; Mexiko; USA; 1900-1999; History